Allele-specific peptide ligand motifs of HLA-C molecules. - Falk, K (1993)
The consensus motifs of HLA-Cw3, -Cw4, -Cw6, and -Cw7 ligands were determined by pool sequencing. Together with information obtained by sequencing of some prominent individual peptides, the results indicate the following: (i) all four HLA-C molecules are associated with peptides. (ii) These peptides adhere to allele-specific motifs that are similar to those of to HLA-A or -B molecules; they have a preferred length of nine amino acids and an anchor residue at the C terminus. (iii) All four HLA-C molecules analyzed exhibit related peptide motifs, although each allelic product shows individual characteristics in fine specificity. (iv) Processing and origin of peptides appear not to be different from that of other class I molecules. (v) No obvious difference at C-terminal position 9 was present in the peptides isolated from the two dimorphic variants of HLA-C that determine dominant resistance to natural killer NK1-specific cells (HLA-Cw4, -Cw6) or to NK2-specific cells (HLA-Cw3, -Cw7) and that differ in two residues in or near the pocket at position 9.